2015
DOI: 10.2106/jbjs.n.00246
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Differences Between Ruptured Anterior Cruciate Ligaments in Young Male and Female Subjects

Abstract: The genes identified in this study as differing distinctly according to sex produce major molecules in the ACL extracellular matrix. Significant upregulation of ACAN and FMOD (which regulate the matrix) and downregulation of WISP2 (which is involved in collagen turnover and production) may account for the weaker ACLs in female compared with male individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Moreover, recent work has linked human ACAN rs1516797 with the risk of ACL injury in both males and females [48]. A separate study revealed ACAN gene expression is up-regulated in ACL samples from female compared to male patients that have undergone ACL repair surgery, suggesting a possible etiology for the observed sex differences among patients with ACL injury [65]. The precise mechanism by which ACAN up-regulation may lead to ligament weakening is currently unclear, though a structural change appears to be the most likely etiology [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent work has linked human ACAN rs1516797 with the risk of ACL injury in both males and females [48]. A separate study revealed ACAN gene expression is up-regulated in ACL samples from female compared to male patients that have undergone ACL repair surgery, suggesting a possible etiology for the observed sex differences among patients with ACL injury [65]. The precise mechanism by which ACAN up-regulation may lead to ligament weakening is currently unclear, though a structural change appears to be the most likely etiology [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The genetically determined features of collagen synthesis have an effect both on the strength of protein bonds in collagen and on the diameter of fibrils [32]. Again, it was proved that genetic characteristics are inherited and more expressed in the female line [33].…”
Section: Mechanism Risk Factors and Programs For Prevention Of Antermentioning
confidence: 98%
“…Recent studies have begun to focus on the importance of the genetic component, considered as an intrinsic factor, in the pathogenesis of non-contact musculoskeletal soft tissue injuries (NCMSTIs) [12][13][14] . All these studies show that there is a marked genetic influence in the nature of an injury 15 , higher than 50% 13,16 . The genetics characteristic of players may also provide information regarding this predisposition of MCL to tear [17][18][19] .…”
Section: Original Articlementioning
confidence: 99%